(untitled) (Nexus International Journal of Science and Education, 2024)
This study investigated the relationship between learner motivation and course engagement among junior high school students. The adopted research design for this study was a quantitative, non-experimental research design utilizing descriptive correlation with regression analysis. A total of 150 students participated in the survey. The findings revealed that the extent of learner motivation among the junior high school students was high, indicating a solid drive and interest in their academic endeavors. Furthermore, the students demonstrated a high level of course engagement, indicating active participation and involvement in their coursework. Notably, the study revealed that there was a significant relationship between learner's motivation and course engagement, highlighting the interdependence of these factors. Furthermore, the study identified intrinsic and utility values as important learning motivation domains that influenced course engagement. These findings underscore the importance of fostering intrinsic and utility values in educational settings to enhance student engagement. Educators should strive to design learning experiences that tap into students' interests, highlight the relevance and practicality of the coursework, and promote a sense of personal value and meaning. By prioritizing and cultivating these aspects, educators could create an environment conducive to high motivation levels and active course engagement among junior high school students.